2022
DOI: 10.3390/geosciences12020069
|View full text |Cite
|
Sign up to set email alerts
|

Arsenic Mineral in Volcanic Tuff, a Source of Arsenic Anomaly in Groundwater: City of Chihuahua, Mexico

Abstract: Arsenic is a naturally occurring trace element that causes many health effects when present in drinking water. Elevated arsenic concentrations in water are often attributed to nearby felsic volcanic sequences; however, the specific rock units to which the groundwater anomalies can be accredited are rarely identified. The groundwater from wells around the city of Chihuahua, Mexico, contains high arsenic content. Arsenic in groundwater increases toward the base rock containing Tertiary volcanic rocks. Through de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Because of the rapid cooling, volcanic gases become trapped in the rock matrix and form a variety of minerals depending on their composition and temperature of formation (Rosenberg, 1988;Wallace 2010). Some minerals that form after sublimation and deposition of volcanic gases include the soluble arsenogoyazite-arseno orencite group (Ren et al, 2022) and aluminum uoride hydrates (Rosenberg, 1988). Besides F and As contained in the felsic rocks, volcanic glasses, and hydrated salt depositions, magmatic uids may crystallize as CaF 2 ( uorite) deposits, some of which occur in the central part of the study area (see Fig.…”
Section: Description Of the Study Areamentioning
confidence: 90%
“…Because of the rapid cooling, volcanic gases become trapped in the rock matrix and form a variety of minerals depending on their composition and temperature of formation (Rosenberg, 1988;Wallace 2010). Some minerals that form after sublimation and deposition of volcanic gases include the soluble arsenogoyazite-arseno orencite group (Ren et al, 2022) and aluminum uoride hydrates (Rosenberg, 1988). Besides F and As contained in the felsic rocks, volcanic glasses, and hydrated salt depositions, magmatic uids may crystallize as CaF 2 ( uorite) deposits, some of which occur in the central part of the study area (see Fig.…”
Section: Description Of the Study Areamentioning
confidence: 90%
“…The permissible concentration of As in drinking water has been set by the WHO at 0.01 mg•dm -3 (WHO, 2022). The enrichment of the environment with As can be caused by both natural sources (Mahimairaja at al., 2005;Kabata-Pendias, 2011;Hasanuzzaman et al, 2015;Ren et al, 2020) and anthropogenic ones, which include, among others, the historical and contemporary ore mining and processing, smelting of non-ferrous metals, as well as various kinds of industry (Krysiak and Karczewska, 2007;Karczewska et al, 2007;Hasanuzzaman et al, 2012;Karc-zewska et al, 2013;Hasanuzzaman et al, 2015;Al-Makishah et al, 2020). The greatest threat to human health caused by arsenic is associated with lithogenically enriched groundwater in several Asian regions, in particular West Bengal, Bangladesh and Taiwan (an endemic area of As-caused "black-foot disease"), where tens of millions of people are considerably affected.…”
Section: Introductionmentioning
confidence: 99%
“…Table 1 about As from geothermal activity. A study conducted near of Chihuahua, México, reported that rocks in area had around 14% of As content, but they also found a substitution process in which phosphorous substitutes As realizing it to aquifers (Ren et al, 2022). In other research carried out in Juventino Rosas, Guanajuato, México, Morales-Arredondo and his colleagues in 2016 found a relationship between high temperature of aquifers and elevated concentration of As, 46 µg/l at 48°C, authors also mentioned that, when high As water from aquifers reaches surface media, can also increase As concentration in different matrixes in environment.…”
Section: Introductionmentioning
confidence: 99%